2012
DOI: 10.1086/665654
|View full text |Cite
|
Sign up to set email alerts
|

The Direct and Ecological Costs of an Ant-Plant Symbiosis

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. Submitted July 12, 2011; Accepted February 3, 2012; Electronically published April 25, 2012 Online enhancement: appendix. Dryad data: http://dx.doi.org/10.5061/dryad.144v45c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 67 publications
4
73
0
5
Order By: Relevance
“…There are costs to engaging in mutualisms (e.g., refs. [77][78][79], and in a gut microbiome context one cost includes nutrient competition between host and microbes (80). A high availability of food allows caterpillars to "skim the cream" (62), assimilating simple nutrients that might otherwise be used by gut microbes and excreting recalcitrant material.…”
Section: Discussionmentioning
confidence: 99%
“…There are costs to engaging in mutualisms (e.g., refs. [77][78][79], and in a gut microbiome context one cost includes nutrient competition between host and microbes (80). A high availability of food allows caterpillars to "skim the cream" (62), assimilating simple nutrients that might otherwise be used by gut microbes and excreting recalcitrant material.…”
Section: Discussionmentioning
confidence: 99%
“…Herbivores are known to affect plant reproduction both directly and indirectly. Direct effects of herbivory result from consumption of plant tissues which, in turn, may cause resource limitation (Strauss et al, 2002). In addition, given the intrinsic link between plant reproduction and defense mechanisms, direct effects of herbivory may also be mediated via trade-offs between investing in reproduction or investing in defenses (Herms and Mattson, 1992; Strauss et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In ant–plant mutualisms, nesting space is a limiting factor for ant colony size (Fonseca 1993) and colony size correlates with defense effectiveness (Heil and McKey 2003; Brouat and McKey 2001; Frederickson et al 2012). However, even when myrmecophytes are at the seedling stage, it has been shown that the first hatched workers of the incipient colony patrol the plant (Brouat and McKey 2000; Moog et al 2005).…”
Section: Discussionmentioning
confidence: 99%